Heterojunctions generated in SnO2–CuO nanocatalysts for improved catalytic property in the Rochow reaction1. Issue 78 (26th August 2015) - Zou, Shanying; Ji, Yongjun; Wang, Guangna; Zhu, Yongxia; Liu, Hezhi; Jia, Lihua; Guo, Xiangfeng; Zhong, Ziyi; Su, Fabing
<x xml:space="preserve">Abstract</x> SnO2–CuO mace-like hybrid nanocatalysts exhibited significantly enhanced performance in the Rochow reaction due to the generated heterojunctions.